Top 10 metrics for life science software good practices - Artaza, Haydee; Chue Hong, Neil; Corpas, Manuel; Corpuz, Angel; Hooft, Rob; Jimenez, Rafael C; Leskošek, Brane; Olivier, Brett G; Stourac, Jan; Svobodová Vařeková, Radka; Van Parys, Thomas; Vaughan, Daniel (F1000Research, 2016)
Metrics for assessing adoption of good development practices are a useful way to ensure that software is sustainable, reusable and functional. Sustainability means that the software used today will be available - and continue to be improved and supported - in the future. We report here an initial set of metrics that measure good practices in software development. This initiative differs from previously developed efforts in being a community-driven grassroots approach where experts from different organisations propose good software practices that have reasonable potential to be adopted by the communities they represent. We not only focus our efforts on understanding and prioritising good practices, we assess their feasibility for implementation and publish them here.
Keywords: Impact; Sustainability; ELIXIR; Software, Best Practices; Evaluation; Metrics